The estimated impact of natural immunity on the effectiveness of human papillomavirus vaccination. Issue 41 (5th October 2015) - Matthijsse, Suzette M.; Hontelez, Jan A.C.; Naber, Steffie K.; van Rosmalen, Joost; Rozemeijer, Kirsten; Penning, Corine; Bakker, Roel; van Ballegooijen, Marjolein; de Kok, Inge M.C.M.; de Vlas, Sake J.
Abstract: Background: Mathematical modelling is used to estimate the effectiveness of HPV vaccination. These estimates depend strongly on herd immunity and thus on naturally acquired immunity, a mechanism of which little is known. We estimated the impact of different vaccination strategies on HPV-16 and HPV-18 transmission and cervical cancer incidence in the Netherlands, considering different acquired immunity mechanisms. Methods: We used the STDSIM microsimulation model, and considered two mechanisms for acquired immunity after infection: (I) full immunity with variable duration; (II) cumulatively decreasing susceptibility to reinfection. Girls aged 13–16 years received vaccination (94.7% efficacy for HPV-16 and 92.3% for HPV-18) during a once-off catch-up campaign with 50% coverage, followed by annual vaccination of 12-year-old girls (60% coverage). Alternative vaccination scenarios included increased coverage, including boys, and lower vaccine efficacy. Results: HPV-16 incidence reduced by 64% under mechanism I and 75% under mechanism II; HPV-18 incidence reduced by 58% and 73%, respectively, and these reductions lead to 48–56% fewer cervical cancer cases. Increasing coverage can lead to over 96% reduction in HPV incidence. Vaccinating boys reduced incidence by 79–89% for HPV-16 and 83–98% for HPV-18 in women. Conclusions: Effectiveness estimates of HPV vaccination differ slightly between different acquired immunity mechanisms, yet these differences are unlikely to affect policy decisions. Offering vaccination to boys as well may be considered to further reduce cancer incidence.